GUGATAN PEMBATALAN LELANG TERHADAP JAMINAN HAK TANGGUNGAN DENGAN CESSIE MENURUT HUKUM PERBANKAN - Novianti, Iswari; Sulistiyantoro, Hariyo (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Banking plays an important role in the global economy. Entrepreneurs often need quick funding to ensure their company's liquidity. However, defaults often occur when banks request an auction from Cessie, the ultimate solution to debt and credit problems. The risk of litigation is very high during auctions and sales. Litigation usually arises from individual dissatisfaction with the defense of contested collateral. The purpose of this study is to find out and analyze the legal remedies used in resolving the dispute of the auction cancellation lawsuit with Cessie and in determining the value of the auction object based on Appraisal. This research is an empirical research using qualitative analysis methods that obtain data through interviews and literature reviews and produce analytical and descriptive data. By analyzing the Cessie auction mechanism in accordance with the policy of the State Savings Bank which caused a dispute in the Surabaya District Court in decision Number 757 / Pdt.G / 2020 / PN SBY